2006
DOI: 10.1016/j.febslet.2006.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae telomerase subunit Est3p binds DNA and RNA and stimulates unwinding of RNA/DNA heteroduplexes

Abstract: Telomerase is a key participant of telomere length maintenance system in majority of eukaryotes. It synthesizes telomere repeats at 3 0 -end of telomere DNA according to its own RNA template. In addition to the reverse transcriptase subunit Est2p and telomerase RNA TLC1, yeast telomerase contain Est1p, necessary for telomerase attachment to telomere and telomerase activation, and Est3p, a subunit with unknown function. We have isolated Est3p and examined its biochemical properties. Est3p binds both DNA and RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…DNA-binding activity and proposed to act as the anchor site for the complex (20)(21)(22). In contrast, not withstanding an earlier report, we and others had been unable to detect a DNA-binding activity for ScEst3 and CaEst3 (9,11,23). The direct physical interaction between Est3 and TEN domain raises the interesting possibility that they may influence each other's nucleic acid-binding properties.…”
Section: Resultscontrasting
confidence: 46%
See 1 more Smart Citation
“…DNA-binding activity and proposed to act as the anchor site for the complex (20)(21)(22). In contrast, not withstanding an earlier report, we and others had been unable to detect a DNA-binding activity for ScEst3 and CaEst3 (9,11,23). The direct physical interaction between Est3 and TEN domain raises the interesting possibility that they may influence each other's nucleic acid-binding properties.…”
Section: Resultscontrasting
confidence: 46%
“…The history for this process is in all likelihood difficult to reconstruct (18). Nevertheless, it appears that similarly drastic changes have transpired in other telomeric proteins (e.g., plant POT1), thus highlighting the malleability of the telomere maintenance machinery in some eukaryotes (23,29).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is suggested in this study that a network of low-affinity interactions among multiple telomerase components is required for the proper assembly of the telomerase holoenzyme. Although S. cerevisiae Est3 has not been shown to bind directly to TLC1, it was shown to be capable of binding RNA (20). Our results are consistent with a scenario in which the telomerase proteins interact with each other and with TER1.…”
Section: Fig 6 Est3 and Reg2 Are Dispensable For Telomerase Activitsupporting
confidence: 86%
“…This possibility was raised by a prior study which reported that an S. cerevisiae GST-Est3 fusion protein, when expressed in E. coli and affinity purified, exhibited an apparent (albeit weak) ability to bind telomeric DNA substrates, as assessed by gel shifts (36). We re-examined this, using NMR chemical shift perturbation, which should reveal chemical shift changes at proximal amide sites, as well as any sites that undergo a conformational change, upon binding of DNA.…”
Section: Resultsmentioning
confidence: 99%